2021
DOI: 10.1007/s10856-021-06491-0
|View full text |Cite|
|
Sign up to set email alerts
|

Oxygen content-related DNA damage of graphene oxide on human retinal pigment epithelium cells

Abstract: Arguments regarding the biocompatibility of graphene-based materials (GBMs) have never ceased. Particularly, the genotoxicity (e.g., DNA damage) of GBMs has been considered the greatest risk to healthy cells. Detailed genotoxicity studies of GBMs are necessary and essential. Herein, we present our recent studies on the genotoxicity of most widely used GBMs such as graphene oxide (GO) and the chemically reduced graphene oxide (RGO) toward human retinal pigment epithelium (RPE) cells. The genotoxicity of GO and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…The main PC parameters measured in the reviewed articles were thickness, lateral size, zeta potential, and hydrodynamic diameter. However, although not so commonly, other parameters such as surface area [ 54 , 55 , 56 ], chemical composition [ 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ], impurity concentration [ 56 , 57 , 63 , 64 , 67 , 68 ], aggregation/agglomeration [ 54 , 60 , 63 , 64 , 69 , 70 ], morphology and/or surface characteristics [ 55 , 57 , 71 , 72 ], thermal stability [ 67 ], elasticity [ 56 ], precipitation in suspension [ 65 ], number of layers [ 54 , 57 , 60 , 61 , 63 , 64 , 71 , 73 , 74 , 75 , 76 , 77 ] hydrophobicity [ …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main PC parameters measured in the reviewed articles were thickness, lateral size, zeta potential, and hydrodynamic diameter. However, although not so commonly, other parameters such as surface area [ 54 , 55 , 56 ], chemical composition [ 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ], impurity concentration [ 56 , 57 , 63 , 64 , 67 , 68 ], aggregation/agglomeration [ 54 , 60 , 63 , 64 , 69 , 70 ], morphology and/or surface characteristics [ 55 , 57 , 71 , 72 ], thermal stability [ 67 ], elasticity [ 56 ], precipitation in suspension [ 65 ], number of layers [ 54 , 57 , 60 , 61 , 63 , 64 , 71 , 73 , 74 , 75 , 76 , 77 ] hydrophobicity [ …”
Section: Resultsmentioning
confidence: 99%
“…In two of the articles, a size-dependent effect was observed, showing particles with smaller lateral size having the strongest genotoxic effect [ 73 , 77 ]. Ou and colleagues [ 68 ] observed that GO induced lower levels of DNA damage than rGO, although at high cytotoxic doses. The authors suggested that oxygen-containing functional groups play an essential role, with saturated C-O bonds reducing genotoxicity in comparison with unsaturated C=O bonds.…”
Section: Resultsmentioning
confidence: 99%
“…Indirect genotoxicity of GFNs mediated by oxidative stress has been explored in vivo and in vitro. For instance, ROS generation and ROS-dependent DNA damage and genotoxicity were observed in human retinal pigment epithelium (ARPE-19) cells after 24 h exposure to GO and rGO [81]. Similarly, GO and rGO can also trigger genotoxicity of female C57BL/6J mice by induction of oxidative stress [82].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…The oxygen-containing functional groups play a key role in the genotoxicity of GFNs [58,[81][82][83]119]. For example, the rGO with lower oxygen content can induce stronger genotoxicity on ARPE-19 cells than these GO with higher oxygen content, suggesting that GO has a better biocompatibility owing to more saturated C-O bonds [81]. The remove of epoxy groups from the GO surface mitigates GO in vivo genotoxicity toward Xenopus laevis tadpoles [58].…”
Section: Surface Propertiesmentioning
confidence: 99%
“…For mammals, GO enters various tissues and organs such as the blood, the gastrointestinal tract, heart, kidney, lung, etc., causing damage to these tissues and organs, resulting in various inflammations, acute allergies and even death [ 14 ]. Due to the unique size and morphology of GO, it easily passes through the cell membrane, leading to the destruction of biomolecules such as nucleic acids, lipids and proteins, which in turn leads to DNA damage and induces genotoxicity [ 15 ]. Therefore, in view of the popularity of GO and the possibility of leakage, the research on GO adsorption is urgently needed.…”
Section: Introductionmentioning
confidence: 99%